Avaliação econômica dos incentivos fiscais e financeiros: uma análise das empresas industriais têxteis localizadas no Rio Grande do Norte, no período de 1999 a 2003 - Silva, Josué Lins e (2005)
This study has as main objective to verify the effect of the tax and financial incentives granted by the brazilian states, specially in the reduction of ICMS on the investment decision of the entities, which in the last years led to the companies to decide new projects in based on the region that presented the better infrastructure beyond lesser tributary expense. For in such was made an economic valuation of the companies with focus in the beneficiary s optics using an adaptation of the Discounted Cash Flow method to measure the impact of the tax incentives in the value of the companies, this study selected the textile industry segment located in the State of Rio Grande do Norte, Brazil. The results indicated that such incentives created addition in the value of the companies, however the inexistence of incentives would not be enough to a negative decision of investment in the Rio Grande do Norte. The smallest difference between the value with and without incentive observed was 8.9%, and the biggest 31.7%, and the average of value aggregation with the tax incentives represented 18.9%